Penaggulangan Masyarakat Korban Bencana Banjir Longsor Menerjang Kampung Cigintung Desa Cibenda Kecamatan Cipongkor Kab. Bandung Barat - FA Suharno (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The aim of this research is to determine the response to landslide floods that occurred in West Bandung Regency, and the evacuation of victims who were injured and died due to landslide floods. As well as restoration of damage to facilities and infrastructure such as community houses, school buildings, mosques and schools due to landslides. The research method uses qualitative methods that describe events at the research location related to landslide victims. The data collection technique is through interviews with several officials and volunteers as well as RW and RW administrators. Observations are carried out to see and observe the conditions at the scene, such as residents' houses that were hit by landslides. Documentation studies related to the research focus in the form of mass media and other online media. The conclusion is that the impact on dealing with landslide flood victims has been implemented by the local government, officials and volunteers. Evacuation of victims with serious and minor injuries as well as those who died have been evacuated to the Cililin Regional General Hospital. Restoration of damaged residents' houses as well as prayer rooms and mosques as a means of worship for Muslims has been carried out. With the natural disaster that resulted in many victims, it became an evaluation material for the West Bandung Regency government, so that it could educate the public.